2006
DOI: 10.1091/mbc.e05-05-0450
|View full text |Cite
|
Sign up to set email alerts
|

Members of the NIMA-related Kinase Family Promote Disassembly of Cilia by Multiple Mechanisms

Abstract: The genome of Tetrahymena thermophila contains 39 loci encoding NIMA-related kinases (NRKs), an extraordinarily large number for a unicellular organism. Evolutionary analyses grouped these sequences into several subfamilies, some of which have orthologues in animals, whereas others are protist specific. When overproduced, NRKs of three subfamilies caused rapid shortening of cilia. Ultrastructural studies revealed that each NRK triggered ciliary resorption by a distinct mechanism that involved preferential depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 58 publications
5
103
1
Order By: Relevance
“…NEK2 is a core component of the human centrosome (Andersen et al, 2003;Fry et al, 1998b), where it regulates a key step in the centrosome cycle, namely centrosome disjunction (O'Regan et al, 2007). Importantly, many NEKs, from fungi to humans, are found at the respective microtubule-organising centres (MTOCs) (for examples, see De Souza et al, 2000;Krien et al, 2002;Mahjoub et al, 2002;Prigent et al, 2005;Wloga et al, 2006). This crucial piece of evidence has led to the hypothesis that NEKs exert their functions through regulation of centrosomes and the microtubule structures that they organise, and that this might not be restricted to dividing cells (Box 1).…”
Section: The Role Of Neks In Mitotic Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…NEK2 is a core component of the human centrosome (Andersen et al, 2003;Fry et al, 1998b), where it regulates a key step in the centrosome cycle, namely centrosome disjunction (O'Regan et al, 2007). Importantly, many NEKs, from fungi to humans, are found at the respective microtubule-organising centres (MTOCs) (for examples, see De Souza et al, 2000;Krien et al, 2002;Mahjoub et al, 2002;Prigent et al, 2005;Wloga et al, 2006). This crucial piece of evidence has led to the hypothesis that NEKs exert their functions through regulation of centrosomes and the microtubule structures that they organise, and that this might not be restricted to dividing cells (Box 1).…”
Section: The Role Of Neks In Mitotic Entrymentioning
confidence: 99%
“…Roles for NEKs in cilia were first revealed through studies in ciliated unicellular eukaryotes, such as Chlamydomonas and Tetrahymena (Bradley and Quarmby, 2005;Mahjoub et al, 2002;Wloga et al, 2006). Compared with non-ciliated fungi, the complement of genes encoding NEKs in these organisms has expanded considerably, and functional studies have suggested that these NEKs might be crucial in regulating ciliary length (Parker et al, 2007).…”
Section: Box 1 Neks In Ciliary Function and Ciliopathiesmentioning
confidence: 99%
“…For instance, in the ciliate Tetrahymena thermophila an extended family of 39 Neks controls cilium length and stability (Wloga et al, 2006). Three NIMA kinases named NRK were identified in Trypanosoma brucei, the parasite responsible for sleeping sickness in human and animals.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 NIMA-related kinase (Nek or Nrk) of Tetrahymena thermophila, Nrk-1 and Nrk-2, localize to the basal bodies and cilia and regulate ciliary length. 3 Fa2p is a NIMA homolog from Chlamydomonas reinhardtii and has been shown to have roles in cell cycle progression and microtubule severing during deflagellation. 4 Recently, Fa2p was found localized to the proximal end of cilia, in both Chlamydomonas and cultured kidney epithelial cells, and its kinase activity is required for deflagellation.…”
mentioning
confidence: 99%